Modelling framework for optimum multiaxial 3D woven textile composites - Brown, Louise P.; Gommer, Frank; Zeng, Xuesen; Long, Andrew C. (2016)
The application of 3D weaves has advantages over conventional uni-directional or 2D woven lay-ups. There is potential to produce near net-shaped preforms and to increase damage resistance due to the presence of through thickness reinforcement. Conventional 3D weaves typically consist of orthogonal yarns interwoven with through thickness binder yarns. This paper describes a feasibility study to find optimum architectures for 3D woven fabrics where some of the normal manufacturing constraints are relaxed. This will provide the basis for development of novel manufacturing methods based on optimum textile architectures. A framework has been developed for the automatic generation and analysis of 3D textile geometries, utilising the open-source pre-processor TexGen. A genetic algorithm is used to select an optimum geometry by evaluating results from finite element simulations using the commercial solver Abaqus. This paper highlights the flexibility of TexGen software to create complex 3D models by means of its Python scripting application programming interface (API). A standard layer-to-layer geometry is used as a starting point to which off-axis yarn rotations, in-plane shift of entire layers and adjustments to binder yarns can be applied. Geometric variables are selected to represent the textile architecture enabling the automation of unit cell creation and finite element analysis. A Genetic Algorithm is used to determine the optimum through thickness binder path, the number and the width of the binders, and yarn angles using a weighted objective function of the material elastic properties. The case studies show that the algorithm is efficient to converge to the optimum fibre architecture.